Youth, the Kenyan state and a politics of contestation. Issue 4 (1st October 2020) - Kimari, Wangui; Melchiorre, Luke; Rasmussen, Jacob
ABSTRACT: This paper introduces the Special Collection 'Youth, the Kenyan state and a politics of contestation'. It focuses on youth and the heterogenous ways this social category responds to inordinate state action. Specifically, we foreground the various roles the Kenyan state has played in the construction and politicization of Kenyan youth across time and space. The introduction frames the papers in the Special Collection within a three-pronged argument: First, while we present youth as heterogeneous social category, we argue that their similar experiences of state surveillance and violence warrant analyzing them through a comparative lens. Secondly, we reject ahistorical renderings of youth politics often presented in youth bulge studies, arguing that such analyses have served to disregard and delegitimize the political grievances of Kenyan youth and flatten the diversity of their political activities. Finally we call for an approach to the study of youth politics, which seeks to expand 'the parameters of the political', taking oft-neglected informal spaces of youth political activity as important discursive and material sites of investigation. Taking these spaces seriously as objects of analysis, the papers provide a nuanced assessment of youth as political actors, which problematize reductive dichotomous narratives of youth politics that pit resistance against co-optation.